THE EFFECT OF ONLINE GAMES AS A MEDIUM TO STUDENTS’ SPEAKING SKILL - Wirawati, Nur; Jabu, Baso; Aeni, Nur (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This study aims to determine the effect of online games as a medium on speaking skills. These 4  fundamental  English  skills  are  speaking,  listening,  reading,  and  writing.  The  majority  of people prefer speaking as their primary mode of communication. In Indonesia, English is a foreign language limited to classroom learning and is rarely used in everyday life, especially in speaking. So, some students need help with mastering English in speaking. Many students nowadays  like  playing  online  games  as  a  hobby  because  Online  Games  have  a  worldwide server, so they can communicate with others using English. Online games have good and bad effects on learning, particularly when learning a new language.  Most use online games as learning techniques and a friendly approach to learning English. This quantitative research uses  a  sample  of  30  students  at  the  language  and  literature  faculty  of  Makassar  State University.  Data  collection  in  this  study  used  a  questionnaire  distributed  by  purposive sampling  technique.  The  data  were  analyzed  using  simple  linear  regression  (F-Test)  and descriptive  statistical  analysis  techniques.  The  results  showed  that  the  influence  of  online games  on  students'  speaking  ability  had  an  effect  of  43.4%.  It  can  also  be  seen  that  the average student playing time is 2 hours, with the type of game most often played being FPS (First Person Shooter). Keywords — Effect, Online Game, Speaking Skill.